(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
A novel, simple, accurate and precise RP-HPLC method for simultaneous determination of levosalbutamol sulfate and theophylline has been developed and validated. Separation was achieved on a Phenomenex; C18 column (250 mm × 4.6 mm i.d., 5 µm) using methanol: 10 mM TBAHS(tetrabutyl ammonium hydrogen sulfate) (50:50, v/v) as mobile phase at flow rate of 1.0 mL.min-1. The UV detection wavelength was 274 nm. The linearity is obeyed over a concentration range of 0.5-150 µg.mL-1 with correlation coefficient of 0.999 for both the drugs. The proposed method was validated by determining accuracy, precision, stability and system suitability parameters. The method was found to be robust. Specificity of the method was determined by subjecting the drugs to various stress conditions like acid, alkali, oxidation, thermal and photolytic degradation. The method was used successfully for the simultaneous determination of levosalbutamol sulfate and theophylline in syrup dosage form.